Effect of Screening and Treatment for Gonorrhea and Chlamydia on HIV Incidence Among Men Who Have Sex With Men in the United States: A Modeling Analysis. Issue 10 (29th October 2022) - Jones, Jeb; Le Guillou, Adrien; Gift, Thomas L.; Chesson, Harrell; Bernstein, Kyle T.; Delaney, Kevin P.; Lyles, Cynthia; Berruti, Andres; Sullivan, Patrick S.; Jenness, Samuel M.
Abstract : Using a network model, we demonstrate that increasing screening for Neisseria gonorrhoeae and Chlamydia trachomatis will result in reductions in HIV incidence among men who have sex with men. Abstract : Background: Previous models have estimated the total population attributable fraction of Neisseria gonorrhoeae and Chlamydia trachomatis (NG/CT) on HIV incidence among men who have sex with men (MSM), but this does not represent realistic intervention effects. We estimated the potential impact of screening for NG/CT on downstream incidence of HIV among MSM. Methods: Using a network model, we estimated the effects of varying coverage levels for sexually transmitted infection screening among different priority populations: all sexually active MSM regardless of HIV serostatus, MSM with multiple recent (past 6 months) sex partners regardless of serostatus, MSM without HIV, and MSM with HIV. Under the assumption that all screening events included a urethral test, we also examined the effect of increasing the proportion of screening events that include rectal screening for NG/CT on HIV incidence. Results: Increasing annual NG/CT screening among sexually active MSM by 60% averted 4.9% of HIV infections over a 10-year period (interquartile range, 2.8%–6.8%). More HIV infections were averted when screening was focused on MSM with multiple recent sex partners: 60% coverage among MSM with multiple recent sex partners averted 9.8% of HIV infections (interquartile range, 8.1%–11.6%). Increased sexually transmitted infection screening among MSM without HIV averted more new HIV infections compared with the transmissions averted because of screening MSM with HIV, but fewer NG/CT tests were needed among MSM with HIV to avert a single new HIV infection. Conclusions: Screening of NG/CT among MSM is expected to lead to modest but clinically relevant reductions in HIV incidence among MSM.